DATA ANALYSIS OF CRYSTAL STRUCTURES OF POLYMORPHIC FORMS USINGMATLAB PROGRAMMING (CAHIERS MAGELLANES-NS, 2024)
Polymorphic form-I and form-II of (E) – 4 - bromo – 2 - [(Phenylimino)methyl] phenol [4B2PMP], commonly known as N-salicylidene, have been identified. Form-I and form-II, respectively synthesized at the temperature of 283 K and 333 K.  In both forms, the molecules show some geometrical structure in different temperatures. In this paper, we employed MATLAB programming to visualize the formation of these molecules' structures and validated our findings via data analysis, hypothesis testing using MATLAB programming.